Analisis Penyelesaian Perselisihan Hubungan Industrial (PHI) secara Litigasi maupun Non-Litigasi - Diah Oktaviani; Icha Nur Safitri; Rosyita Putri Septiviani; Syifatul Wardah Alhumairoh; Lutfi Aprilia; Badrut Tamam (Rechtenstudent, 2023)
Industrial relations disputes (PHI) are of great concern to the public. In principle, disputes can be resolved by the parties themselves or third parties. One of the industrial relations disputes is a strike. A Work Strike is a planned strike and industrial action carried out to stop or slow down work. This dispute will cause a decrease in company productivity, therefore it is necessary to resolve it so that company activities return to normal. Writing this paper uses the literature review method by browsing literature online consisting of theses, journals and books, relating to the resolution of industrial relations disputes. The result of this paper is that PHI is divided into two types, namely disputes of interest and disputes of rights. PHI resolution must be truly objective and fair. Settlement of PHI can be done in court or outside State court. Cassation is the cancellation of a lower court decision, a decision made on the basis of errors and omissions in the Supreme Court's decision. A work strike is an example of PHI. Striking workers must be warned, must not violate the law, and conditions must be met.